Profiling of transcriptional regulators associated with starch biosynthesis in sorghum (Sorghum bicolor L.) - Xiao, Qianlin; Huang, Tianhui; Cao, Wan; Ma, Kuang; Liu, Tingting; Xing, Fangyu; Ma, Qiannan; Duan, Hong; Ling, Min; Ni, Xianlin; Liu, Zhizhai (Frontiers in Plant Science, 2022)
Starch presents as the major component of grain endosperm of sorghum (Sorghum Bicolor L.) and other cereals, serving as main energy supplier for both plants and animals, as well as important industrial raw materials of human beings, and was intensively concerned world widely. However, few documents focused on the pathway and transcriptional regulations of starch biosynthesis in sorghum. Here we presented the RNA-sequencing profiles of 20 sorghum samples at different developmental stages to dissect key genes associated with sorghum starch biosynthesis and potential transcriptional regulations. A total of 1708 highly expressed genes were detected, including 416 in grains, 736 in inflorescence, 73 in stalk, 215 in root, and 268 genes in leaf. Besides, 27 genes encoded key enzymes associated with starch biosynthesis in sorghum were identified, including 6 for ADP-glucose pyrophosphorylase (AGPase), 10 for starch synthases (SSs), 4 for both starch-branching enzymes (SBE) and starch-debranching enzymes (DBEs), 2 for starch phosphorylases (SPs), and 1 for Brittle1 (BT1). In addition, 65 transcription factors (TFs) that highly expressed in endosperm were detected to co-express with 16 out of 27 genes, and 90 cis-elements were possessed by all 27 identified genes. Four NAC TFs were cloned, and the further assay results showed that 3 of them could in vitro bind to CACGCAA motif within the promoters of SbBt1 and SbGBSSI, two key genes associated with starch biosynthesis in sorghum, functioning in the similar ways that reported in other cereals. These results confirmed that sorghum starch biosynthesis might share the same or similar transcriptional regulations that documented in other cereals, and provided informative references for further regulatory mechanism dissection of TFs involved in starch biosynthesis in sorghum.